2013
DOI: 10.1126/science.1229277
|View full text |Cite
|
Sign up to set email alerts
|

Germline DNA Demethylation Dynamics and Imprint Erasure Through 5-Hydroxymethylcytosine

Abstract: Mouse primordial germ cells (PGC) undergo sequential epigenetic changes and genome-wide DNA demethylation to reset the epigenome for totipotency. Here, we demonstrate that erasure of CpG methylation (5mC) in PGCs occurs via conversion to 5-hydroxymethylcytosine (5hmC), driven by high levels of TET1 and TET2. Global conversion to 5hmC initiates asynchronously among PGCs at embryonic day (E) 9.5-E10.5 and accounts for the unique process of imprint erasure. Mechanistically, 5hmC enrichment is followed by its prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
619
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 698 publications
(669 citation statements)
references
References 25 publications
26
619
3
5
Order By: Relevance
“…Given that loss of imprinting is a known driver of developmental disease and cancer [64,65], its occurrence in naive cells would render them unsafe for clinical and transgenics applications. ICR erasure in primordial germ cells is thought to involve TET protein action [66][67][68][69], and as such, it is not unreasonable to expect that loss of imprinting in naive ESCs could be exacerbated by supplementation of vitamins A and C. This means that in order to strike a balance between imprinting fidelity in naive pluripotent stem cells and the efficiency at which they are derived, fine-tuning of vitamin levels and TET activity may be required …”
Section: Vitamins a And C In Regenerative Medicine And Mammalian Transgenmentioning
confidence: 99%
“…Given that loss of imprinting is a known driver of developmental disease and cancer [64,65], its occurrence in naive cells would render them unsafe for clinical and transgenics applications. ICR erasure in primordial germ cells is thought to involve TET protein action [66][67][68][69], and as such, it is not unreasonable to expect that loss of imprinting in naive ESCs could be exacerbated by supplementation of vitamins A and C. This means that in order to strike a balance between imprinting fidelity in naive pluripotent stem cells and the efficiency at which they are derived, fine-tuning of vitamin levels and TET activity may be required …”
Section: Vitamins a And C In Regenerative Medicine And Mammalian Transgenmentioning
confidence: 99%
“…Recent studies have demonstrated that TET family proteins have potential roles in epigenetic regulation during germ cell reprogramming and meiotic entry of early germ cells through modification of 5mC to 5hmC, [37][38][39][40] an important member of the TET family is TET1 which catalyzes the conversion of 5mC to 5hmC during PGC reprogramming. 41 We thus evaluated the expression levels of TET1 at different culture stages.…”
Section: Effects Of Acta On Dedifferentiation Of Sdscs To Epiblast-limentioning
confidence: 99%
“…In this scenario, direct and simultaneous exposure of three generations (i.e., the pregnant mother, her fetus, and the fetuses' primordial germ cells) might be responsible for the increased disease risk seen in each generation. Alternatively, and if more than three generations are affected, research is revealing how inheritance of epigenetic modifications to the genome may be responsible (Hackett et al 2013). …”
Section: Transgenerational Transmissionmentioning
confidence: 99%